2021
DOI: 10.1002/slct.202004567
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of NiFe2O4@AC/UiO‐66(Zr) for Enhancement of the Photocatalytic Performance of Alizarin Yellow R Under Visible‐light

Abstract: In this study, NiFe2O4@AC/UiO‐66(Zr) composites were successfully prepared with different ratios of UiO‐66(Zr) as support for NiFe2O4@AC, (1 : 1), (2 : 1) and (3 : 1) named NiFe2O4@AC/UiO‐66(Zr)‐1, NiFe2O4@AC/UiO‐66(Zr)‐2 and NiFe2O4@AC/UiO‐66(Zr)‐3, respectively. The prepared composites were characterized by X‐Ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), X‐Ray photoelectron spectroscopy (XPS), thermogravimetric analysis (TGA), scanning electron microscopy (SEM), Brunauer–Emmett–Telle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 68 publications
(65 reference statements)
1
11
0
Order By: Relevance
“…After each cycle, the catalyst was collected and washed with deionized water three times before the next cycle. It is distinct that the BiOBr/Bi 2 S 3 @CeMOF preserved good stability with a decrease of 10.2±1.91 % in reduction efficiency after the five cycles (Figure S3a, ESI) that demonstrate the efficiency and stability of the prepared catalyst as well as the applicability of the prepared photocatalyst for industrial applications [55] . Besides, the recovered photomaterial was characterized by XRD to examine the possible change in their crystallization after five cycles.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…After each cycle, the catalyst was collected and washed with deionized water three times before the next cycle. It is distinct that the BiOBr/Bi 2 S 3 @CeMOF preserved good stability with a decrease of 10.2±1.91 % in reduction efficiency after the five cycles (Figure S3a, ESI) that demonstrate the efficiency and stability of the prepared catalyst as well as the applicability of the prepared photocatalyst for industrial applications [55] . Besides, the recovered photomaterial was characterized by XRD to examine the possible change in their crystallization after five cycles.…”
Section: Resultsmentioning
confidence: 91%
“…It is distinct that the BiOBr/ Bi 2 S 3 @CeMOF preserved good stability with a decrease of 10.2 � 1.91 % in reduction efficiency after the five cycles (Figure S3a, ESI) that demonstrate the efficiency and stability of the prepared catalyst as well as the applicability of the prepared photocatalyst for industrial applications. [55] Besides, the recovered photomaterial was characterized by XRD to examine the possible change in their crystallization after five cycles. The XRD pattern (Figure S3b, ESI) exhibits the same characteristic peaks of the BiOBr/Bi 2 S 3 @CeMOF before the photoreduction process.…”
Section: Proposed Photocatalytic Mechanism and Stability Studymentioning
confidence: 99%
“…This XRD pattern agreed with the formation of Ni nanoparticles (JCPDS 04-0850). [37] The peaks of the anatase TiO 2 of catalytic materials appear at 2θ values of 25.3°(101), 37.8°(004), 48.1°(200), 53.8°( 105), 55.2°(211) and 63.0°(204). TiO 2 supported on cellulose metallized showed anatase form indicating it has not changed its crystal structure.…”
Section: Chemistryselectmentioning
confidence: 99%
“…Other examples of MOF-based S-scheme photocatalysts include investigations of the activity of NiFe 2 O 4 @AC/UiO-66 in the degradation of alizarin yellow R 185 and nitrogen-doped carbon quantum dots (NDCQDs)/ZIF-8 in the decomposition of MB. 186 Khalk et al 186 found that NDCQDs/ZIF-8 photocatalyst has an increased dye adsorption and, therefore, is characterized by an improved photocatalytic activity in the degradation of MB compared to the pristine MOF.…”
Section: •−mentioning
confidence: 99%
“…Other examples of MOF‐based S‐scheme photocatalysts include investigations of the activity of NiFe 2 O 4 @AC/UiO‐66 in the degradation of alizarin yellow R 185 and nitrogen‐doped carbon quantum dots (NDCQDs)/ZIF‐8 in the decomposition of MB 186 . Khalk et al 186 .…”
Section: Mof‐based Heterojunctions As Photocatalysts For the Degradat...mentioning
confidence: 99%